Bioactive compounds and antioxidant potential of different accessions of Euterpe oleracea and Euterpe precatoria from the active açaí germoplasm bank (Research, Society and Development, 2022)
The Active Germplasm Bank of Açaí (Euterpe spp), BAG Açaí, of Embrapa Amazon Eastern (Belém, PA, Brazil) has a large number of genotype of three species, of which two E. oleracea and E. precatoria subsidize the genetic improvement. This study aimed to investigate the chemical differences of the fruits of eight genotype of both species conserved in the BAG through the parameters of pulp yield, total lipids, total phenolic compounds, total flavonoids, total monomeric anthocyanins and the evaluation of the antioxidant capacity (ABTS radical scavenging). In general, the genotype of E. precatoria presented ranges of lipid contents (19-53%), total phenolic compounds (769-2414 mg/100 g), total flavonoids (164-325 mg/100 g), total monomeric anthocyanins (76-1822 mg/100 g) and antioxidant capacity (35-96 µM equivalent of Trolox/g) were higher than genotypes of E. oleracea, with accession PL01 (E. precatoria) being the most prominent. Of the species E. oleracea, genotype L2PL5 presented the highest content of total monomeric anthocyanins (736 mg/100 g), total flavonoids (306 mg/100 g) and antioxidant capacity (53 µM trolox equivalent/g). Therefore, accessions PL01 and L2PL5 were the most promising materials to continue the genetic improvement research.